A Sociolinguistics Analysis of Education Register in Independent Learning (The Newest System of Education in Indonesia) - Iim, Oktaviani (Interdisciplinary Explorations in Research Journal, 2023)
The existence of the newest independent curriculum education system which is interrelated raises registers, especially in the field of education. This study aims to describe the register of education in independent curriculum. Independent Curriculum is made an object because it is the newest curriculum in Indonesia and more than 2,500 schools have implemented it. This study uses a qualitative descriptive method with a sociolinguistic approach. The data was taken using qualitative data, namely objects in the form of registers found on the official Youtube account of the Indonesian Ministry of Education and Culture and official literature from the Ministry of Education and Culture. The technique used is the technique of listening, taking notes, and concluding. Based on the analysis that has been done, it can be concluded that in the lingual register there are 6 lingual registers. There are 17 closed registers and 8 open registers.